Up‐regulation of plasma lncRNA CACS15 distinguished early‐stage oral squamous cell carcinoma patient. (24th August 2020) - Zhang, Xinyu; Guo, Bing; Zhu, Yun; Xu, Wanlin; Ning, Shangbo; Liu, Liu
Abstract: Objective: To study the role of LncRNA CASC15 in oral squamous cell carcinoma. Results: In the present study, we showed that plasma CASC15 was up‐regulated in stage I and II oral squamous cell carcinoma patients than in oral ulcer patients and healthy controls, while no significant correlation was found between oral ulcer patients and healthy controls. Up‐regulation of plasma CASC15 distinguished oral squamous cell carcinoma patients from oral ulcer patients and healthy controls. LncRNA MEG3 was inversely correlated with CASC15 in oral squamous cell carcinoma tissues. In oral squamous cell carcinoma cells, CASC15 over‐expression led to the inhibited expression of MEG3, and MEG3 over‐expression did not alter CASC15 expression. MEG3 over‐expression decreased, while CASC15 over‐expression increased the proliferation rate of oral squamous cell carcinoma cells. In addition, MEG3 over‐expression attenuated the effects of CASC15 over‐expression. Conclusion: Therefore, CASC15 over‐expression may serve as a potential diagnostic biomarker for oral squamous cell carcinoma, and CASC15 may promote oral squamous cell carcinoma cell proliferation by down‐regulating MEG3.